A Conceptual Study of Aging w.s.r. to Jara”: An Ayurvedic Insight - Singh, Archana; Dwivedi, Ashutosh; Dubey, Pooja (International Research Journal of Ayurveda & Yoga, 2024)
Aging is a natural, multidimensional process of physical, psychological, and social change. In Ayurveda aging is known as “Jara", synonymic with “Vardhakya” means increasing age. In literatures Jara (aging) is accepted as Swabhava Bala Pravarat/ Swabhava Nispratyanika Vyadhi (natural unavoidable disease) and divided in two type’s Kalaja Jara (chronological aging) and Akalaja Jara (premature aging).The Kalaja Jara is parirakshana krita, which means that it occurs at the proper age even after following all the preventive measures. Whereas Akalaja jara is said to be due to Aparirakshana - Krita, which means that it occurs before the mentioned age in absence of any preventive measures or due to various causative factors. The Ayurvedic concept of aging has been dealt with, keeping in view of the Tridosas, Saptadhatus, Malas, Srotas, Indriyas, Agni and Ojas. When all of these are in homeostasis the body functions well. But due to old age, increase of Vata, vitiation of Pitta and decrease in Kapha causes an impact on the various other components of body, thus allowing the aging to take over. Aging before time can be prevented through Ayurveda. The pathophysiology of aging is mostly dependent on diet and lifestyle, therefore process of aging can be slowed down by planning of appropriate diet, routine and lifestyle.